(3cJGH GdeYGQLs - (3GdgPdj, GdMdj, CHh GdbGSe, fLe GdOjf, GdeMbb GdMdj, LYaQ Hf GdMSf Hf jMji Hf GdMSjf, J(B676(3g`s ((3eMeO Hf OQhjT YhV GdMdjs)
(3ChdgG (B:s
(3CMeO Gddg Ydi SGHZ fYeJg (B... (3hHYO Pdc aEfg JcQQ ef LeGYI ef GdCUMGH (B... (3GdJeGS eNJUQ aj GdCUhd eTJed Ydi Gdege ef eWGdHg(B... (3hgh jTJed Ydi CHhGH YTQI(B...s
(3BNQgG (B:s
(3hZjQ Pdc ef GdMGOjK GdOGdI Ydi GdefY ef bJd GdeSde heY hLhO GdfU dG GYJHGQ HZjQg (B... (3hGddg GdYGUe(B. (3Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI HQbe(B: 4503s
(3GdPQjYI HQbe(B: 4503s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs